Zmiana płci w świetle prawa polskiego - Zielonacki, Andrzej (Wydział Prawa i Administracji UAM, 1988)
The article discusses the problems of the change of sex in Polish law in the contex of comparative aspects. A main topic is the regulation of the way of changing sex in the law on civil status acts. Only a few countries (Sweden, West Germany, Italy, The Netherlands, Austria) adopted appropriate legislative acts in that respect. Polish law, like most other European legal systems, does not address that issue in the statutory form. Hence, numerous problems arise with respect to the judicial change of sex of transsexuals. Contrary to the Supreme Court's view allowing to apply by analogy the provisions on correction cf a birth certificate, the author proposes to use for that purpose a declaratory action regulated in Art. 189 of the Civil Procedure Code. Accepting a prevailing opinion that sexual integrity is one of personal interests protected by the civil law and that a natural person has personal rights to those interests, the author draws the conclusion that Art. 189 of the Civil Procedure Code may be used by a person showing the traits of transsexualism. At the same time the author points to the possibilities of regulating the issues of the change of sex in the future law on medical care and medical profession.
The change of sex in polish law